Chrysin Enhances Anti-Cancer Activity of Jurkat T Cell and NK-92 Cells Against Human Breast Cancer Cell Lines - Durmus, Ezgi; Ozman, Zeynep; Ceyran, Ibrahim Halil; Pasin, Ozge; Kocyigit, Abdurrahim (WILEY-V C H VERLAG GMBH, 2024)
Chrysin, a naturally occurring flavonoid in plant and bee products, demonstrates notable biological activities, including anti-cancer effects. These properties are partially attributed to its capability to activate immune cells. This study focused on exploring the immunomodulatory potential of chrysin on NK-92 and Jurkat-T cells targeting breast cancer cells (BCC). Chrysin leads to activation of NK-92 and T cells facilitated by the addition of human recombinant IL-2 and PHA-M. The anti-cancer efficacy of chrysin on these immune cells was evaluated in a co-culture setup with EGF-stimulated MCF-7 and MDA-MB-231 cells. Findings revealed that chrysin notably increased the cytotoxicity of NK-92 and T cells towards MCF-7 and MDA-MB-231 cells, with the most significant impact observed on MCF-7 cells (20 %). The activation of NK-92 cells, marked by increased IFN-gamma production and CD56 expression, correlated with enhanced secretion of cytokines. Additionally, the activation of these cells against BCC was linked with elevated levels of granzyme-B, TNF-alpha, and nitric oxide (NO). Similarly, the cytotoxic activation of Jurkat-T cells against BCC was characterized by increased production of granzyme-B, IL-2, and IFN-gamma. Consequently, these results support the hypothesis that chrysin significantly contributes to the activation and functional enhancement of NK-92 and T-cells against two distinct BCC lines. image
Keywords: Chrysin; NK cells; T cells; Breast cancer; NK cell cytotoxicity; T cell cytotoxicity; NITRIC-OXIDE SYNTHESIS; IN-VITRO; CYTOKINE PRODUCTION; IFN-GAMMA; INDUCTION; FLAVONOIDS; GROWTH; PHYTOHEMAGGLUTININ; MACROPHAGES; MECHANISMS; Biochemistry & Molecular Biology; Chemistry